Optimal Planning of Battery Electric Buses for Reliable Services - Elkholy, Sama; Shaaban, Mostafa F.; Ali, Abdelfatah (2023 International Electrical Engineering Congress (iEECON), 2023)
Battery electric buses (BEB) are a strong alternative for climate change mitigation due to their potential to reduce fossil fuel consumption. This paper introduces a deterministic optimization model for the optimal selection of the number of buses and opportunity chargers of an all-electric bus fleet constrained by a specified route cycle, number and duration of stops, frequency, service time, and BEB model. The optimization model is based on a BYD K9 40' Transit BEB fleet. The bus's power consumption model is generated and the problem is formulated subject to the constraints mentioned above. The optimization problem is formulated as a Mixed Integer Non-Linear Programming (MINLP) and is solved using General Algebraic Modeling System (GAMS) program. The main results are obtained in two cases: when the bus's air conditioning is turned on and when it is turned off. For the first case, various results are obtained by varying the problem parameters at a time within a certain range to observe how the critical problem variables are affected. The obtained results demonstrate the effectiveness of the proposed planning approach.